Maternal Serum Resistin Is Reduced in First Trimester Preeclampsia Pregnancies and Is a Marker of Clinical Severity. (2nd October 2015) - Christiansen, Michael; Hedley, Paula L.; Placing, Sophie; Wøjdemann, Karen R.; Carlsen, Anting L.; Jørgensen, Jennifer M.; Gjerris, Anne-Cathrine; Shalmi, Anne-Cathrine; Rode, Line; Sundberg, Karin; Tabor, Ann
Abstract : Objective : To examine whether resistin levels in first trimester maternal serum are associated with insulin resistance or preeclampsia (PE). Methods : A case-control study of maternal serum resistin concentration conducted using 285 normal pregnancies and 123 PE pregnancies matched for gestational age, parity and maternal age. Samples were taken in gestational weeks 10 +0 –13 +6 . Results : There was a negative correlation between resistin and clinical severity of PE, but no correlation with IS, TNF-α, body mass index, birth weight and pregnancy length. Conclusions : Resistin is reduced in first trimester of PE pregnancies, particularly in severe PE. Inflammation and IS cannot explain this phenomenon.